Peningkatan Pengetahuan Masyarakat Desa Wisata Tentang Kepariwisataan Di Kabupaten Manggarai: Increasing Knowledge of Tourism Village Communities About Tourism in Manggarai Regency - Rudiyanto, Roseven (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2024)
Tourism villages can also be seen as a tourism concept that emphasizes the participation of local communities. However, community participation in developing tourist villages faces various challenges, such as a lack of knowledge and ability in managing tourist villages. Manggarai Regency is a district in East Nusa Tenggara Province which has 29 tourist villages. Therefore, this activity aims to increase community knowledge in managing tourist villages. The implementation of this PKM uses lecture, discussion and field practice methods. The training material consists of 8 materials, namely 1) Regional Tourism Development Policies and Programs for Tourism Village Development, 2) Tourism Villages in the Tourism System, 3) Building Tourism Aware Village Communities Through Sapta Pesona, 4) Building Management Institutions Tourism Villages, 5) Development and Management of Community-Based Tourism Products, 6) Application of cleanliness, health, safety and environmental sustainability in the management of tourist villages, 7) Evaluation of Tourism Village Management Practices Based on Training Participants' Experiences, and 8) Management of Empowered Tourism Villages Competitive and Sustainable. Based on the results of the pre-test and post-test, it shows that there has been an increase in the knowledge of the training participants. Thus, holding tourism village management training can increase community knowledge.